COMPARISON OF POTASSIUM ELECTROLYTE LEVELS IN BLOOD SPECI-MEN USING VACUUM TUBE CLOSE RED AND YELLOW AT TOTO KABILA HOSPITAL BONE BOLANGO DISTRICT - Sry Rahmatia Rauf; Muh. Rizman Naim; Haryanto (Journal of Health, Technology and Science (JHTS), 2021)
Blood electrolyte levels in the tube will decrease after 30 minutes of blood collection due to the hemolysis process at a rate of about 7 mg/dl per hour. This study aims to determine the comparison of potassium electrolyte levels in blood specimens using red and yellow vacuum tubes at Toto Kabila Hospital, Bone Bolango Regency.The method in this study used descriptive with a quantitative approach and the method used in this study was accidental sampling with a sample of 30 patients who were to be studied. The method in this study used a quantitative approach with a descriptive type of research and the sampling technique used was accidental sampling with a sample of 30 patients who were to be studied. The results of the comparison of potassium levels in vacuum tubes with red lids and vacuum tubes with yellow covers showed normal potassium levels in 24 samples or (80%) and abnormal potassium levels in 6 samples or (20%) with the results of the Mann -With a test on comparisons of potassium levels in tubes with red caps and yellow caps showing that .0.099 > 0.05 so that it can be concluded that there is nothing significant about potassium examination using vacuum tubes with red lids and vacuum tubes with yellow lids.